MMP−2 Expression in Skeletal Muscle after Strength Training - Deus, A.P. L.; Bassi, D.; Simões, R. P.; Oliveira, C. R.; Baldissera, V.; de Cássia Marqueti, R.; Araujo, H.S. S.; Arena, R.; Borghi-Silva, A. (International Journal of Sports Medicine, 2012)
The aim of this study was to assess the effects of resistance training on ladders (RTL) on MMP−2 expression and blood lactate concentration [La−]. 30 male (3 months of age), albino rats were divided into 3 groups: sedentary control (SC, n=10), low resistance exercise training (Low-IntRT, n=10) and high-intensive exercise training (High-IntRT, n=10). Animals of High-IntRT were submitted to a progressively increasing overload in relation to body weight until exhaustion, while the Low-IntRT group performed the same exercise regimen with no external load. The program had a frequency of 3 times per week over 8 weeks. MMP−2 expression of tibialis anterior muscle and [La−] were measured. While there was a significant increase of MMP−2 (pro-form) in both groups, only High-IntRT significantly increased MMP−2 in active-form (p<0.05). Both trained groups exhibited an increase in [La−] when compared to controls, however, the increase in [La−] was significantly higher in the High-IntRT compared to Low-IntRT (p<0.05). Strong correlation was found between MMP−2 (active form) and [La−] in High-IntRT (r=0.91). RTL in using low and high-intensity exercise can serve as a model to demonstrate different responses of MMP−2 expression in an animal model. It appears active form expression of MMP−2 is modulated by exercise intensity.
Keywords: resistance exercise; blood lactate; matrix metalopeptidases; ladder exercise